MINERALOGICAL-GEOCHEMICAL FEATURES OF MAGNETITE OCCURRENCES IN SERPENTINITES OF THE KALKAN AREA (MAIN URALIAN FAULT ZONE, SOUTH URALS) - D.E. Saveliev (Минералогия)
Chemical and mineralogical composition of magnetite occurrences from serpentinites of the Kalkan mélange area of the Main Uralian Fault zone (South Urals) is studied. Abundant Cu minerals including native copper, Cu sulfides (covellite, bornite, minerals of the chalcocite-digenite series), chlorides (nantokite), Cu carbonates and Cu silicates are found in magnetite ores. Magnetite also contains abundant inclusions of cobaltpentlandite, rare Ag and Bi sulfides, heazlewoodite and awaruite. All magnetite occurrences host relicts of chromites, the composition of which (moderate to high Cr / (Cr + Al) values) indicates strong depletion of a peridotite protolith, which formed in the upper mantle below a forearc basin. A two-stage formation model of the magnetite occurrences is suggested. At an early stage, the disseminated magnetite with inclusions of Cu-Fe-Co sulfides formed under the influence of metalliferous fluids in serpentinized ultramafic rocks at the bottom of the oceanic basin. During collision, serpentinites were tectonized with the formation of small bodies of massive magnetite ores and Cu, Ag and Bi sulfides and native minerals.